Toxic cyanobacteria and their toxins in standing waters of Kenya: implications for water resource use - Kotut, Kiplagat; Ballot, A.; Krienitz, L. (My University, 2006)
Phytoplankton biodiversity studies in Kenya's standing waters were carried out between 2001 and 2003. Toxin producing cyanobacteria were recorded in twelve water bodies. Microcystis and Anabaena were the most common species in freshwaters while Anabaena and Anabaenopsis were common in alkaline saline lakes. Seven lakes with cyanobacteria blooms and a hot spring had detectable levels of microcystins and anatoxin-a. Cell bound microcystins (LR equivalents) concentration ranged from 1.6-19800 microgg(-1) Dry Weight (DW) while anatoxin-a varied from below the limit of detection to 1260 microgg(-1) DW. In alkaline-saline lakes, microcystins and anatoxin-a were also present in stomach contents and liver samples of dead flamingos. Monoculture strains of A. fusiformis from Lakes Sonachi and Bogoria had detectable levels of microcystins while anatoxin-a was present in strains isolated from Lakes Sonachi, Bogoria and Nakuru. Two freshwater sites, Nyanza Gulf (L. Victoria) and Lake Baringo recorded cyanotoxin concentration exceeding WHO'S upper limit of 1.0 microgl(-1) for drinking water. The results confirm that cyanotoxins could have played a role in the mortality of flamingos in Lakes Bogoria and Nakuru. The implications of these findings on water resource use, measures to be taken to reduce the risk of exposure and eutrophication control steps to reduce cyanobacteria bloom formation are considered in this paper.
Keywords: algal blooms; Cyanotoxins; Eutrophication; flamingos; Kenya; phytoplankton